Analysis of Chemical Properties in Soil in the Selected Sites in Samoa - Amosa, Bernadette P.; Imo, Taema; Latu, Faainuseiamalie; Ieremia, Roya; Simi, Ietitaia; Gese, Gese (European Journal of Applied Sciences, 2022)
Chemical properties of soil are of importance as they influence the fertility of soil i.e., what types of plants can grow and determines how well they will grow; as well as the extent to which organisms habituating will survive and withstand changes presented by any change. Since the pool of soil health data is still in the process of advancing, this study proceeded to build a baseline that would be useful for future research. Thus, the main research question was diverted directly to determine the health of Soils in Samoa through the assessment of its individual property, i.e., chemical properties. In addition, results were used to generate inferential analysis to denote climatic changes to the soil tested. The following are the overall results for the chemical properties across the four sites during the 6 months period: pH= 6.4 ± 0.16; EC= 35 mS/s ± 4.55; CEC= 21.22 meq/100g ± 4.13; SOC= 2.14% ± 0.73 and C:N ratio= 16:1± 4.01.